2005
DOI: 10.1162/105474605323384681
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Teleoperation of a Mobile Robot: A User Study

Abstract: The problem of teleoperating a mobile robot using shared autonomy is addressed: an onboard controller performs close range obstacle avoidance while the operator uses the manipulandum of a haptic probe to designate the desired speed and rate of turn. Sensors on the robot are used to measure obstacle range information. A strategy to convert such range information into forces is described, which are reflected to the operator's hand via the haptic probe. This haptic information provides feedback to the operator in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…We consider feedback force based on the obstacle range information only (environmental force feedback). In conventional approach [1] the following basic law was used for calculating the force feedback:…”
Section: Overview Of Mobile Robot Teleoperationmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider feedback force based on the obstacle range information only (environmental force feedback). In conventional approach [1] the following basic law was used for calculating the force feedback:…”
Section: Overview Of Mobile Robot Teleoperationmentioning
confidence: 99%
“…The force f e is applied to operator through master device to the opposite direction of the obstacle. Experiments proved that the usage of environmental feedback force improves safety of teleoperation by reducing the number of collisions [1]. But, it was also shown that feedback force with constant feedback gain degrades the accuracy of mobile robot motion control [5].…”
Section: Overview Of Mobile Robot Teleoperationmentioning
confidence: 99%
See 2 more Smart Citations
“…They also proved the passivity of the system which guaranteed the stability of haptic interaction. Similar approach was proposed by Lee et al in [2]. It was proposed to convert obstacle range information from mobile robot into force field reflected to human-operator.…”
Section: Introductionmentioning
confidence: 99%